Crystal structure of hydrocortisone acetate, C23H32O6. Issue 1 (11th January 2017) - Kaduk, James A.; Gindhart, Amy M.; Blanton, Thomas N.
Abstract : The crystal structure of hydrocortisone acetate has been solved and refined using synchrotron X-ray powder diffraction data, and optimized using density functional techniques. Hydrocortisone acetate crystallizes in space group P 21 (#4) with a = 8.85173(3) Å, b = 13.53859(3) Å, c = 8.86980(4) Å, β = 101.5438(3)°, V = 1041.455(6) Å 3, and Z = 2. Both hydroxyl groups form hydrogen bonds to the ketone oxygen atom on the steroid ring system, resulting in a three-dimensional hydrogen bond network. The powder pattern has been submitted to ICDD for inclusion in the Powder Diffraction File™.